Mentoring Nurses in Political Skill to Navigate Organizational Politics - Wanda Montalvo; Mary W. Byrne (Hindawi Limited, 2016)
Objective. The aim of this study was to describe and analyze the correlations between mentoring functions and political skill development among nurses who have earned or are candidates for a Ph.D. or doctorate of nursing practice (DNP) degree. Background. The healthcare system is in flux; future generations of Ph.D. and DNP nurse leaders will be required to demonstrate political acumen. Political skill to navigate organizational politics has had limited research within nursing. Methods. A cross-sectional research design using a web-based survey of 222 nurses who have earned or are candidates for a Ph.D. or DNP. This study utilized two validated tools to measure mentoring functions and political skill. Results. The response rate was 52% (n=115) of which 86 were Ph.D. and 29 were DNPs. An informal mentoring relationship was described by 62% of the respondents and formal mentoring by 35% of the protégés; only 25% (n=74) established a mentoring contract. Mentoring score showed significance for total political skill and moderate effect on the networking ability. The mentoring functions of advocacy, career development facilitation, learning facilitation, and friendship were found to correlate significantly with total political skill scores. Conclusions. This study established a benefit for nurses who have earned or are candidates for a Ph.D. or DNP from mentoring to support political skill development.